Preoperative Evaluation of Primary Hemostasis in Patients with Thrombocytopenia Using the Thrombostat 4000 - Edsfors Åleskog, Anna; Killander, Andreas; Olsson, Karin; Eriksson, Lars; Kristensen, J örgen (Seminars in Thrombosis and Hemostasis, 1995)
It is difficult to estimate the risk of hemorrhage that may follow an invasive or surgical procedure in patients with thrombocytopenia or platelet dysfunction. Conventional functional tests for the evaluation of primary hemostasis have been questioned. We have evaluated the in vitro bleeding time (IVBT) using the Thrombostat 4000 in 25 patients with thrombocytopenia in order to estimate the risk of bleeding following an invasive or surgical procedure. Using the IVBT, it was possible to suggest and evaluate preoperative treatment in order to restore primary hemostasis. All patients studied had their operations without bleeding complications. From these observations we conclude that the IVBT is a convenient and useful tool in the evaluation of primary hemostasis in these patients.
Keywords: bleeding time; Thrombostat 4000; thrombocytopenia; surgery; platelets